ON THE SUITABILITY OF MODULAR MULTILEVEL CONVERTER (MMC) IN HIGH VOLTAGE DIRECT CURRENT (HVDC) TRANSMISSION SYSTEM - Kadandani, Nasiru B.; Hassan, Sahalu; Abubakar, Isiyaku (FUDMA Journal of Sciences, 2023)
Transmitting bulk electrical energy over long distance by overhead transmission lines or submarine cables using high voltage direct current (HVDC) transmission system offers more flexibilities such as controllability of power flow and robustness against disturbances. Both current source converter (CSC) and voltage source converter (VSC) configurations have been considered in HVDC system. The former is used in HVDC transmission system involving stiff grid networks of higher ratings while the latter is commonly used in connecting to a weak grid. As such, special applications of HVDC such as connection between two or more weak grids and connection of wind power plants require the VSC configuration. However, in the conventional VSC configuration, the converter arm would have to be designed with large number of semiconductor switches that can block the full DC-bus voltage. However, with the evolution of modular multilevel converter (MMC) as a member of VSC family, sub-module (SM) chopper cells are used. This paper investigates the suitability of MMC in HVDC transmission system. The paper shows that the MMC configuration can generate any desired voltage levels required to synthesize a smooth output waveform, thus eliminating the need of heavy filters, has modularity in both hardware and software and generates very low harmonics.